(untitled) (Research, Society and Development, 2021)
The objective of this article is to investigate the influence of associating vitamin D in the treatment of severe cases of COVID-19. Several studies match on the importance of having a good immune system to avoid the risk of disease progression, enhancing the importance of having vitamin D in the human body. In this review, we will discuss the latest evidence on the metabolism and mechanism of action of vitamin D in the immune system, its biological targets, its importance in the immunological role, its health benefits, and its relationship with the pathogenicity of COVID-19, particularly in severe cases. However the large quantity of scientific data related to the topic, the result of this review shows that there is still having a lack of investigations that correlate genetic data and viral responses, in addition to randomized clinical studies that appraises the influence of vitamin D supplementation on the control and progression of the clinical condition of COVID-19.